Succession of Microbial Decomposers Is Determined by Litter Type, but Site Conditions Drive Decomposition Rates - Buresova, A; Kopecký, Jan; Hrdinkova, V; Kamenik, Z; Omelka, M; Ságová-Marečková, Markéta (Applied and environmental microbiology, 2019)
Soil microorganisms are diverse, although they share functions during the decomposition of organic matter. Thus, preferences for soil conditions and litter quality were explored to understand their niche partitioning. A 1-year-long litterbag transplant experiment evaluated how soil physicochemical traits of contrasting sites combined with chemically distinct litters of sedge (S), milkvetch (M) from a grassland, and beech (B) from forest site decomposition. Litter was assessed by mass loss; C, N, and P contents; and low-molecular-weight compounds. Decomposition was described by the succession of fungi, Actinobacteria, Alphaproteobacteria, and Firmicutes; bacterial diversity; and extracellular enzyme activities. The M litter decomposed faster at the nutrient-poor forest site, where the extracellular enzymes were more active, but microbial decomposers were not more abundant. Actinobacteria abundance was affected by site, while Firmicutes and fungi by litter type and Alphaproteobacteria by both factors. Actinobacteria were characterized as late-stage substrate generalists, while fungi were recognized as substrate specialists and site generalists, particularly in the grassland. Overall, soil conditions determined the decomposition rates in the grassland and forest, but successional patterns of the main decomposers (fungi and Actinobacteria) were determined by litter type. These results suggest that shifts in vegetation mostly affect microbial decomposer community composition.IMPORTANCE Anthropogenic disturbance may cause shifts in vegetation and alter the litter input. We studied the decomposition of different litter types under soil conditions of a nutrient-rich grassland and nutrient-poor forest to identify factors responsible for changes in the community structure and succession of microbial decomposers. This will help to predict the consequences of induced changes on the abundance and activity of microbial decomposers and recognize if the decomposition process and resulting quality and quantity of soil organic matter will be affected at various sites.
Keywords: Soil; Ecosystem; RNA, Ribosomal, 16S; půdní mikrobiologie; Forests; biodiverzita; Bacteria; Fungi; lesy; ekosystém; RNA ribozomální 16S; půda; mikrobiota; Grassland; pastviny; houby; Microbiota; Biodiversity; Soil Microbiology